Navigating Career Development: A Qualitative Analysis of Planning, Exploration, and Decision-Making in Young Adults - Saeed , Bushra; Naqvi, Irum (IUB Journal of Social Sciences, 2024)
The research article studies the significance and meaning of career development among young adults. Young adults in developing countries are facing multiple issues of instability and disadvantages and very limited research has been conducted in these countries on exploring career development tasks in their early years of young adulthood. The study focuses on the tasks related to their career planning, exploration, and decision-making that have to be accomplished in the early years of their young adulthood. Data was required from young adults aged 19 to 23 years (M = 21.40, SD = 1.75) to get knowledge about these career developmental tasks. The technique of Focus Group Discussions was used for a better understanding of the career developmental tasks. Term career development was used to acquire information about career planning, exploration, and decision-making tasks in the sample. The findings of the study help prepare young adults to complete career developmental tasks and manage the complexities of their career development process.